PHYTOCHEMICAL EVALUATION AND ANTIBACTERIAL POTENTIAL OF TRICHOSANTHES TRICUSPIDATA ROOT EXTRACTS AGAINST HUMAN PATHOGENIC BACTERIA: Pharmaceutical Science-Pharmacognosy - SAPNA BHARDWAJ; RASHMI (International Journal of Life Science and Pharma Research, 2022)
Trichosanthes tricuspidata (family: Cucurbitaceae) commonly known as Lal indrayan or shvetpushpi and found at an elevation of 1200 to 2300 m. It grows as a large climber, often attaining a height of 9-10 meters. T. tricuspidata has been widely used for curing asthma, migraine, fever, diabetic carbuncles and other maladies. The present study was aimed to do phytochemical screening and antibacterial activity of different extracts of T. tricuspidata roots. The antibacterial activity of root extracts was tested against Gram positive and Gram negative pathogens viz. Pseudomonas aeruginosa (MTCC 1036), Klebisilla pneumonia (MTCC 432), Staphylococcus aureus (MTCC 96) and Streptococcus mutans (MTCC 497). The ethanol, 50%ethanol and water extracts from mature roots of plant were screened for their chemical constituents and antibacterial activity. Ethanolic extract showed the presence of alkaloids, carbohydrates, glycosides, saponins and triterpinoids and maximum antibacterial activity against Klebisilla pneumonia (MTCC 432) at 1mg/100ml concentration. The antibacterial potential of the plant was then compared with standard gentamycin.